OPTIMIZING THE JOURNAL OF INSPIRASI EKONOMI, UNIVERSITAS TIMOR TOWARDS AN ACCREDITED NATIONAL JOURNAL - Nurul Huda; Syaefudin Aziz; Yeremias Lake; Budiman Baso; Hernur Yoga Priyambodo (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agug, 2023)
The Journal Inspirasi Ekonomi is a scientific publication media that has a vital role in realizing the vision, mission and objectives of the Management study program, Faculty of Economics and Business, Universitas Timor. This activity aims to improve the quality of the Journal of Inspirasi Ekonomi so that its management is by the standards of the national journal accreditation institution (ARJUNA) and the SINTA accreditation process can be carried out immediately. The method used in this community service activity is Participatory Action Research (PAR), namely identifying crucial problems that could hinder the accreditation process and then repairing and completing them. The activities carried out by the servant in this activity are compiling and making publication ethics statements, creating a google scholar profile and optimizing indexation, updating information on the OJS Journal of Inspirasi Ekonomi page, conducting scientific paper writing webinars to obtain articles and increase readability, visits and citations. After carrying out this activity, the Inspirasi Ekonomi Journal, Universitas Timor, has met the standards and can be submitted for accreditation to the national journal accreditation institution (ARJUNA).